2018
DOI: 10.3847/1538-4357/aabbae
|View full text |Cite
|
Sign up to set email alerts
|

Low Metallicities and Old Ages for Three Ultra-diffuse Galaxies in the Coma Cluster

Abstract: A large population of ultra-diffuse galaxies (UDGs) was recently discovered in the Coma cluster. Here we present optical spectra of three such UDGs, DF7, DF44, and DF17, which have central surface brightnesses of μ g ≈24.4-25.1 mag arcsec −2 . The spectra were acquired as part of an ancillary program within the SDSS-IV MaNGA Survey. We stacked 19 fibers in the central regions from larger integral field units (IFUs) per source. With over 13.5 hr of on-source integration, we achieved a mean signal-to-noise … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
79
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(87 citation statements)
references
References 76 publications
8
79
0
Order By: Relevance
“…Only about a dozen higher surface brightness Coma UDGs have measured spectroscopic stellar population properties ( Ferré-Mateu et al (2018); Ruiz-Lara et al (2018); Gu et al (2018); Chilingarian et al (2019)). These studies generally found intermediate-to-old ages and low metallicities.…”
Section: Udg Stellar Massesmentioning
confidence: 99%
“…Only about a dozen higher surface brightness Coma UDGs have measured spectroscopic stellar population properties ( Ferré-Mateu et al (2018); Ruiz-Lara et al (2018); Gu et al (2018); Chilingarian et al (2019)). These studies generally found intermediate-to-old ages and low metallicities.…”
Section: Udg Stellar Massesmentioning
confidence: 99%
“…In Figure 8 we compare the luminosityweighted age distribution of galaxies in our sample to that of UDGs observed in the Coma (Gu et al 2018;Ruiz-Lara et al 2018;Ferré-Mateu et al 2018) and Virgo (Pandya et al 2018) clus- Considering that we only have luminosityweighted ages, the results from the our analysis are expected to be biased toward the youngest populations within a galaxy. Therefore, a few different, non-exclusive scenarios can explain the additional fraction of UDGs with young ages.…”
Section: The Luminosity-weighted Ages Of Field Udgsmentioning
confidence: 99%
“…Prole et al 2019), are available for many UDGs but are of limited value in determining the properties of the stellar populations, while spectroscopy, which can provide the necessary information, is only available for a small number of galaxies (e.g. Martínez-Delgado et al 2016;Kadowaki et al 2017;Ruiz-Lara et al 2018;Ferré-Mateu et al 2018;Gu et al 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Koleva et al 2008;Larsen et al 2017;Wilkinson et al 2017;Conroy et al 2018) or even by simultaneously fitting both photometry and spectroscopy to fully utilise the information contained in the spectroscopy (Leja et al 2017). A previous example of combining the stellar population constraints from optical photometry and spectroscopy can be found in Gu et al (2018) who used both to place stronger constraints on the old ages of three ultra-diffuse galaxies.…”
Section: Ages From Combining Photometry and Spectroscopymentioning
confidence: 99%